A psychological support group for parents in the care of families with gender diverse children and adolescents. (January 2021) - Caldarera, Angela M; Davidson, Sarah; Vitiello, Benedetto; Baietto, Chiara
Parenting gender diverse children and adolescents can be a challenging experience, entailing doubts about how to protect and support them during their development. Parental reactions impact on the child's sense of security and well-being. Therefore, when caring for families with gender diverse children, it is important to offer support to parents. In this article we present an experience with a 12-month support group for parents of young people who attended the service for gender identity development at a paediatric hospital. We describe the group structure and methodology, together with the process for evaluating the intervention. At 6-month intervals, parents were asked to indicate the most important topics that had emerged during the monthly sessions. At 12 months, they completed a semi-structured feedback questionnaire about their experience in the group, including possible difficulties encountered. Thematic analysis showed an evolution in time, with participants taking a more complex perspective on gender diversity and the needs of their children, while feeling more able to deal with the uncertainties related to gender identity development. After attending the group, parents reported feeling less lonely, more confident, and better able to communicate with their children. They related these positive changes to the opportunity of sharing experiences and mutual learning. This feed-back provides preliminary evidence that the psychological support group was perceived to be a useful resource by parents of gender diverse young people.